OP0116 Cost-effectiveness and cost-utility analysis of treat-to-target versus usual care in early rheumatoid arthritis: Results of the dream registry. (23rd January 2014) - Vermeer, M.; Kievit, W.; Kuper, I.; Braakman-Jansen, A.; Bernelot Moens, H.; Zijlstra, T.; den Broeder, A.; van Riel, P.; Fransen, J.; van de Laar, M.
Abstract : Background: Treat-to-target (T2T) has proven to be more effective in achieving remission in early rheumatoid arthritis (RA) patients than usual care [1]. However, T2T has not been fully implemented in daily clinical practice yet. Moreover, it is unknown whether T2T is cost-effective. Objectives: To analyse the cost-effectiveness and cost-utility of a T2T strategy aiming at remission (Disease Activity Score in 28 joints (DAS28) <2.6) compared to usual care in early RA over the first two years of the disease. Methods: Two early RA inception cohorts including patients who fulfilled the ACR 1987 criteria were compared. The T2T group (n=261) consisted of patients from the DREAM remission induction cohort and was treated according to a protocolized treatment strategy aiming at DAS28 remission. The usual care group (n=213) consisted of patients from the Nijmegen early RA inception cohort and was treated without DAS28-guided, protocolized treatment decisions. For both groups, direct medical costs were collected and compared with gain in effectiveness (DAS28 remission) and quality adjusted life years (QALYs) (EQ-5D utility estimated from the HAQ) over two years of follow-up. Results: T2T produced a higher remission percentage (64.4% vs. 34.7%) and a larger gain in QALYs (median (IQR) 1.45 (1.24-1.55) vs. 1.39 (1.18-1.53), p=0.037) than usual care. The total mean (SD) costs per patient were €4.807 (7.434) in the T2T group and €3.806 (5.761) in the usual care group. The incremental cost-effectiveness ratio was €3.340 per patient in remission. The incremental cost-utility ratio was €18.259 per QALY. The figure presents the cost planes which show the relation between A) the differences in effectiveness and costs and B) the differences in utility and costs of T2T versus usual care. Anti-TNF therapy was given to more T2T patients (21.5% vs. 15.0%) and was prescribed earlier in the disease process, compared to usual care. Conclusions: This quasi-experiment showed that over the first two years of treatment, T2T is associated with higher costs but also with substantial higher effectiveness. We conclude that T2T is cost-effective in daily clinical practice. References: [1] Schipper et al, Ann Rheum Dis. 2011 (In press). Disclosure of Interest: None Declared